Um equilíbrio de poderes: distribuição populacional e direitos paroquiais em Coimbra (1377-1385) - Campos, Maria Amélia Álvaro de (2018)
In 1377 King Fernando ordered the repopulation of the citadel of Coimbra, in the centre of Portugal, requiring residents of the outskirts to move inside the town walls and to rebuild derelict properties there, which were granted to them to that effect. Taken in the aftermath of the invasion of the kingdom by Castilian troops and shortly after the only Portuguese university had been transferred from Coimbra to Lisbon, this measure effected a redistribution of the population and of parochial rights and tithes, which created important jurisdictional tensions between Coimbra’s intramural and suburban parishes. Their sources of income threatened, the latter strove to obtain a regime of exception that allowed them to keep collecting their parochial rights from their former parishioners. This gave rise to several judicial conflicts with the citadel’s parishes. Building on the analysis and contextualisation of these lawsuits, this essay proposes a novel explanation of the dynamics of population distribution in fourteenth-century Coimbra. In particular, it problematizes the perception of the will of town dwellers in choosing their place of residence; the spiritual and fiscal consequences of demographic redistribution; and the intervention of lay and ecclesiastical powers in the organisation of social and private life in Coimbra.